Properties and Microstructure of the Ru-Coated Carbon Nano Tube Counter Electrode for Dye-Sensitized Solar Cells - Han, Jeungjo; Yu, Byungkwan; Noh, Yunyoung; Suh, Young Joon; Kim, Moon J.; Yoo, Kicheon; Ko, Min Jae; Song, Ohsung (AMER SCIENTIFIC PUBLISHERS, 2014)
In this study, we investigated the performance of dye-sensitized solar cells (DSSCs) with the ruthenium (Ru) coated multi-walled carbon nanotube (MWCNT) on the counter electrode (CE). High purity MWCNT (0.01 similar to 0.06 g) was sprayed on glass/fluorine-doped tin oxide (FTO). Then 30 nm-thick Ru thin films were coated on a MWCNT template at low temperature by atomic layer deposition (ALD) using RuDi and O-2 as precursor to prepare Ru-CNT CE and the 0.45 cm(2) DSSC device of glass/FTO/TiO2/Dye (N719)/electrolyte (C6DMII, GSCN)/Ru-CNT CE was fabricated. The surface morphology of CEs and the energy conversion efficiency of the DSSC device were characterized by scanning electron microscope (SEM), high-resolution transmission electron microscope (HRTEM), and photocurrent-voltage (I-V) measurement. We confirmed that effective surface of the CE increased linearly as the amount of MWCNT spray increased and the crystallized Ru was deposited very conformally around the MWCNT nano template. Moreover, the efficiency of the DSSC increased up to 3.3% as the amount of MWCNT increased.
Keywords: ATOMIC LAYER DEPOSITION; LOW-COST